Svend Borberg: Punktummet, der ikke blev sat: Uopdagede værker fra en dramatiker med europæisk udsyn - Kallenbach, Ulla; Lawaetz, Anna (Peripeti, 2022)
Svend Borberg: The punctuation mark that was never written. Undiscovered works by a playwright with an international outlook This article focuses on two hitherto undiscovered, unrealized works by one of the most remarkable, and controversial Danish playwrights and theatre critics from the interwar period, Svend Borberg. Borberg was a rare modernist and internationally oriented voice in Danish theatre, and the two works, the biblical comic opera Susanna and the pantomimic ballet, Stambul brænder [Stambul Burning] adds not only an important missing link in Borberg’s oeuvre, but also in those of his collaborators, the composers Knudåge Riisager and Alexander Tscherepnin.